Using the Photovoice Approach to Empower Pakistani women participating in the PakCat program to become promoting agents of healthy eating habits in Catalonia - Saba Mohammad-bibi; Cristina Vaque crusellas (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Immigrant women of Pakistani origin are among one of the most invisible ethnic groups residing in Catalonia. They are also among the most at-risk groups for obesity and type 2 diabetes. Aim: To promote healthy eating habits among the Pakistani population in Barcelona. Method:The study was a mixed-method randomized control trial (RTC) conducted in Badalona and Santa Coloma de Gramenet, two of Barcelona’s most populous municipalities with 87% of Catalonia’s foreign Pakistani population. The research involved 137 women, 70 from Casa Àsia and 67 from FundacióAteneuSant Roc, who were recruited through the support of organizations like The FundacióAteneu Santa Roc and Casa Àsia. The study was developed in five phases: dissemination and recruitment, pilot study, baseline data collection, implementation of the food education intervention, and evaluation. Participants were divided into small subgroups (12-15 women) and participated in 10 educative sessions based on the Transtheoretical model for 10 weeks. The final session was dedicated to the Photovoice methodology, which involved participants capturing an image of their favorite dish and responding to the SHOWeD questions. The images were then presented to a multilingual nutritionist who addressed any concerns during the photovoice process. Results: The study analyzed 70 images of healthy dishes and identified improvements in dietary patterns. The Harvard Healthy Plate method was applied to prepare lunches and dinners, with vegetables in raw and cooked forms and often accompanied by yoghurt sauce. The carbohydrate portion consisted of whole grain chapati or rice, while the protein portion was mostly composed of lentils, eggs, and chicken. The participants prepared their meals with olive oil and water, and mostly consumed seasonal fruit for dessert. Red meat was minimally present in the dishes, with lentils, eggs, chicken, and fish being the main protein sources. Participants learned various culinary techniques to prepare fish, such as fish and vegetable curry and masala fish.Nutritious breakfasts were presented, with whole grains, fruits, vegetables, nuts, and seeds, and milk tea (chai) accompanied by fruit and nuts. Many participants presented healthy substitutes for traditional sweet dishes, stating that maintaining their intake is important for their heritage. Practical Implication: The Harvard Healthy Plate approach, a structured dietary method, has been shown to improve dietary habits. Participants learned to prepare balanced meals using vegetables, protein sources, and whole grain carbohydrates. They reduced red meat consumption and incorporated protein-rich alternatives like lentils, fish, and eggs. They also learned cooking techniques for fish, incorporating nutritious seafood into their diet. They introduced healthy breakfast choices, substituting traditional foods with healthier ones, and using olive oil and water for cooking. Conclusion: This study demonstrates that photovoice is a practical approach to assess the improvements in the dietary habits of Pakistani women and to empower them to become ambassadors of healthy eating habits for their community. Keywords: Photovoice, Pakistani women, empowerment, community-based participatory research (CBPR)